Awards As Signals - Bruno S. Frey; Susanne Neckermann (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Awards are widespread in all countries and are prevalent both in the public sphere and in the private sector. This paper argues, and empirically supports, that awards serve public functions and economists should take them seriously. Using a unique cross-country data set, we suggest that awards serve as signals. Awards are more prevalent the more difficult the position and status of an individual is to observe due to an anonymous and globalized setting.
Keywords: A13; D63; J33; 330; Awards; Signals; Status; Anonymity; Globalization